A preliminary study of associations between discomfort intolerance, pain severity/interference, and frequency of cannabis use among individuals with chronic pain. (2nd January 2020) - Kosiba, Jesse D.; Mitzel, Luke D.; Zale, Emily L.; Zvolensky, Michael J.; Ditre, Joseph W.
Abstract: Background: Cannabis use is more common among individuals with chronic pain, and is often used to relieve physical discomfort. However, little is known about factors that are associated with cannabis use among individuals with chronic pain, and there is reason to suspect that perceptions of discomfort intolerance (DI) play an important role in pain-cannabis relations. Method: The goal of this study was to conduct an initial examination of perceived DI, pain severity, and pain-related interference in relation to frequency of cannabis use among individuals with chronic pain. Specifically, we hypothesized that pain severity/interference and factors of DI (avoidance and intolerance), would each be positively associated with cannabis use frequency. Results: Participants (N = 109; 44% male; Mage = 27) endorsed chronic pain and at least one instance of lifetime cannabis use. Most participants characterized their chronic pain as high intensity and low disability, and the two most commonly reported frequencies of cannabis use were "less than monthly" (n = 38), and "daily/almost daily" (n = 32). Results indicated that discomfort avoidance (but not discomfort intolerance), pain severity, and pain-related interference were each independently and positively associated with frequency of cannabis use. Conclusions: These preliminary findings suggest that continued examination of perceived discomfort avoidance in relation to co-occurring pain and cannabis use is warranted. Future research should replicate these results among treatment-seeking pain patients who are prescribed medical cannabis.